2012
DOI: 10.3390/md10081812
|View full text |Cite
|
Sign up to set email alerts
|

Sea Anemone (Cnidaria, Anthozoa, Actiniaria) Toxins: An Overview

Abstract: The Cnidaria phylum includes organisms that are among the most venomous animals. The Anthozoa class includes sea anemones, hard corals, soft corals and sea pens. The composition of cnidarian venoms is not known in detail, but they appear to contain a variety of compounds. Currently around 250 of those compounds have been identified (peptides, proteins, enzymes and proteinase inhibitors) and non-proteinaceous substances (purines, quaternary ammonium compounds, biogenic amines and betaines), but very few genes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
199
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(207 citation statements)
references
References 148 publications
(163 reference statements)
2
199
0
6
Order By: Relevance
“…They contain a variety of toxic proteins and peptides, including potent toxins affecting the transient receptor protein vanilloid (TRPV1), acid-sensing ion channels, voltage-gated Na + (Na V ) and K + channels, as well as secondary metabolites [4]. Recently, the ectodermal gland cells were also reported as a toxin production compartment in sea anemones [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They contain a variety of toxic proteins and peptides, including potent toxins affecting the transient receptor protein vanilloid (TRPV1), acid-sensing ion channels, voltage-gated Na + (Na V ) and K + channels, as well as secondary metabolites [4]. Recently, the ectodermal gland cells were also reported as a toxin production compartment in sea anemones [5].…”
Section: Introductionmentioning
confidence: 99%
“…and Shaw (K V 3.) subfamilies and also intermediate conductance calcium-activated K + channels [4]. Potassium channel toxins of this type have been characterized from the venom of sea anemones of different families (Actiniidae, Hormathiidae, Stichodactylidae and Thalassianthidae) and can be subdivided into subtype 1a and subtype 1b, having four and eight amino acid residues respectively between the second and third cysteine residues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Like all cnidarians, hydroids and anemones possess millions of harpoon-like stinging cells (nematocysts) that contain nerve-or cardiotoxins and are used to capture and immobilise prey (Sher & Zlotkin 2009, Frazão et al 2012, Cegolon et al 2013). Hydroids and anemones are relatives of the hydrozoan and scyphozoan jellyfish that have been identified as important agents of gill disorder in farmed salmon .…”
Section: Health and Disease Risksmentioning
confidence: 99%
“…Among all classes, the Kunitz-type inhibitors are well characterized of them, possibly due to their abundance in several creatures [13,15,16]. Many studies reported that animal venoms contain Kunitz-type serine protease inhibitors [12,[17][18][19]. Similarly, Kunitz-type as well as Ascaris-type serine protease inhibitors have been reported to be present in scorpions, and most of them have been identified by cDNA cloning and transcriptomic analysis [10,11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%